Overview of Game Effect on Dynamics of Speed Development in Girls of Primary School Age - С. І. Марченко; С. В. Краснокутський (OVS LLC, 2016)
The reserch objective is to analyze the effect of game means on the dynamics of speed abilities development in girls of the second-fourth grade. Materials and Methods. The participants in the experiment were 104 female pupils of the second grade (n=32), third grade (n=32), and fourth grade (n=40).  Research Methods: theoretical analysis and collation of scientific and methodological literature, method of control testing, pedagogical experiment, methods of mathematical statistics. Results. The study proves the necessity to use game exercises that are rationally balanced in terms of orientation, power and scope with regard to the individual constitutional peculiarities of children in order to achieve the best pedagogical effect in the development of speed abilities. The games performed with the highest swiftness contribute to the development of speed. These exercises require the best efforts, which is why their duration must not exceed 5-10 seconds, the rest intervals must be relatively large - from 40 to 60 seconds. The rest time and load time must not be constant. Conclusions. Selective and directed development of motor abilities requires taking into account the duration and pace (intensity) of the performance of the physical exercises.